Calling their bluff: Expressed and revealed preferences of top college graduates entering teaching in Argentina - Alejandro Ganimian; Mariana Alfonso; Ana Santiago (Inter-American Development Bank (IDB), 2013)
Many school systems today are trying to attract top college graduates into teaching, but little is known about what dissuades this target group from entering the profession. This study randomly assigned applicants for a highly-selective alternative pathway into teaching in Argentina either to a survey about their motivations for applying to the program or to surveys that revealed information about their future pay or working conditions. The study finds that applicants who received information about pay or working conditions were much more likely to report that they intended to drop out of the selection process, but were no more likely to actually drop out. This can be explained by the temporary salience effects of the informational prompts. Applicants with higher undergraduate grade point averages and/or scores in the selection process, however, were both more likely to report that they will drop out and to actually do so.
hdl:11319/4633
Keywords: I20; J44; C93; 330